The Effect of Time Pressure, Workload and Work-Life Balance in Work From Home Situation on Reduce Audit Quality with Moderating Variables of Work Motivation in BPK RI Perwakilan Sulawesi Utara - Nur Isnaeni; Jullie J. Sondakh; Hendrik Gamaliel (DINASTI RESEARCH, 2023)
This study aims to determine the effect of time pressure, workload, work-life balance on Reduce Audit Quality with work motivation as a moderating variable in the North Sulawesi Representative office of the Audit Board of the Republic of Indonesia (BPK RI). The approach used in this research is quantitative by using primary data through questionnaires. Respondents in this study were auditors at the office of North Sulawesi Representative of BPK RI. Analysis of the data used is Partial Least Square (PLS) using the SmartPLS version 3.0 software program. The results of this study indicate that: 1) Time pressure has a positive and significant effect on Reduce Audit Quality; 2) Workload has a positive and significant effect on Reduce Audit Quality; 3) Work-life balance has a negative and significant effect on Reduce Audit Quality; 4) Work motivation weakens the effect of Time Pressure on Reduce Audit Quality in the North Sulawesi Representative office of BPK RI; 5) Work Motivation weakens the influence of Workload on Reduce Audit Quality in the North Sulawesi Representative office of BPK RI; 6) Work Motivation strengthens the influence of Work-Life Balance on Reduce Audit Quality in BPK Perwakilan Sulawesi.